From Hamlet to Holmes: literary detective tradition - Nozen, SeyedehZahra; Isaxanli, Hamlet; Amani, Bahman (Linguistics and Culture Review, 2021)
Exposed to the mystery of his father’s suspicious death, young Hamlet followed the riddle of solving it in the longest tragedy of Shakespeare. By suspension and the lengthy nature of detective works, Shakespeare seems to have initiated a new subgenre in drama which may have later on been converted into an independent subgenre in the novel by Edgar Allan Poe, Sir Arthur Conan Doyle, and Agatha Christie through their imaginative characters, Auguste Dupin, Sherlock Holmes and the pair of Hercules Poirot with Miss Marple respectively. Fyodor Dostoevsky may have also spread the net of Hamletian subtext in his Crime and Punishment. Plotting a perfect crime by the murderers and the public approval of the plan, on one hand, and the inconvincible mind of the hero which ultimately undo the seemingly unsolvable puzzle, on the other, construct the very core of all aforementioned works of Shakespeare, Poe, and Doyle. The unanticipated and unpredicted findings of either Holmes or Hamlet defeat the expectations of the audience and bring the runaway justice back to her groom.